Physiological assessment of seed and seedling growth of vinegar - Ribeiro Amaro, Hugo Tiago; Santos de Souza David, Andréia Márcia; Silva Neta, Izabel Costa; Alves, Dorismar David; da Silva, Fernando Gomes (Comunicata Scientiae, 2013)
The experiment was conducted at the Laboratory of Seed Analysis Unimontes, with the objective to evaluate physiological seed and seedling growth of vinegar. Seeds from mature fruits collected from plants from the experimental area Unimontes. We used a completely randomized design (CRD) with four replications in a factorial 2 x 3 consists of two temperatures (25 and 30 ° C) and three periods of soaking in distilled water (0, 24 and 48h). the variables analyzed were: seed germination, first count, speed and germination, seedling length, fresh weight and dry weight of seedlings. The pre- soaking the seeds in distilled water for 48 hours and constant temperature at 30 ° C increments promote the germination and seedling growth of vinegar.